Special stock market segments for small company shares in Europe - What went wrong? - Sebastian Rasch (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1994)
Special stock market segments for small company shares were established by all major European stock exchanges during the 1980's. After showing a remarkable success during the first years of their existence - both in the primary as well as in the secondary market - these segments today suffer from increasing illiquidity. The stock exchange authorities in London and in Amsterdam have therefore decided to close down their stock markets for smaller companies. This paper takes a closer look at the current situation of these stock market segments throughout Europe and discusses the causes for their decline.
Keywords: 330; Klein- und Mittelunternehmen; Aktienmarkt; OTC-Handel; Branchenentwicklung; Westeuropa